(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study explores the perceptions and gratifications of college teachers in Tirunelveli City regarding the digital payment system. Through a comprehensive examination, the research aims to gain insights into how college educators perceive and experience digital payment methods. The investigation involves primary and secondary data sources, with primary data collected through a structured questionnaire administered directly to the teachers. Secondary data are drawn from various sources, including textbooks, journals, and materials available on digital payment system websites. The findings of this study aim to contribute valuable insights into the perspectives and satisfaction levels of college teachers in Tirunelveli City regarding the adoption and use of digital payment systems.